Quranic Ethics and the Role of Social Interpretation in Raising Awareness Against the Dangers of Behavioral Deviations: An Analytical Study on a Sample of Al-Qadisiyah University Students (Journal of the College of Basic Education, 2026)
Social interpretation has played a role in guiding and reducing negative phenomena in society by addressing the Muslim human mind and directing him towards following the right path, and paying attention to presenting the correct principles of healthy social life, and warning against the dangers of behavioral deviations such as violence, smoking, and the spread of drugs. This is what prompted the research to conduct an applied study. Analytical and determining the impact of social interpretation in reducing behavioral deviations among young people, as they are the most affected group The external group is the group that is able to influence and will have a role in society. The research aims to identify the role of Quranic morals and social interpretation in raising awareness against the dangers of behavioral deviations from the students’ point of view